Implementation of Talking Chips Type Cooperative Model to Improve Student Collaboration in Class X History Learning at SMA Negeri 7 Semarang - Anjani, Syafira Dewi; Amin, Syaiful (LPPM STKIP Kusuma Negara, 2025)
This study to overcome the lack of collaboration and student interest in learning history in class X SMA Negeri 7 Semarang by applying the Talking Chips cooperative learning model. The research method used is descriptive qualitative approach, this study collected data from grade X students and 1 history subject teacher for three meetings through observation, interview, Focus Group Discussion (FGD), and documentation. The results showed a significant increase in students’ active participation (from 65% to 90%), a change in students’ positive perception of history, and the development of critical thinking skills. The Talking Chips model contributes by providing empirical evidence regarding the effectiveness of innovative learning models in improving collaboration and creating a more interactive history learning experience that is relevant to 21st century skills.